1997
DOI: 10.1074/jbc.272.50.31872
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cysteine Pairs within the Amino-terminal 5% of Apolipoprotein B Essential for Hepatic Lipoprotein Assembly and Secretion

Abstract: There is growing evidence that the amino-terminal globular domain of apolipoprotein B (apoB) is essential for lipoprotein particle formation in the hepatic endoplasmic reticulum. To identify the structural requirements for its function in lipoprotein assembly, cysteine (Cys) pairs required to form the seven disulfide bonds within the amino-terminal 21% of apoB were replaced in groups or individually by serine. Substitution of Cys pairs required for formation of disulfide bonds 1-3 or 4 -7 (numbered from amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 34 publications
3
37
1
Order By: Relevance
“…Transfection studies have suggested that apoB segments containing sequences lacking the ␤␣1 domain were unable to be secreted (13) or else secreted poorly (14). Mutational analysis has identified critical disulfide linkages within the ␤␣1 domain that are essential for efficient secretion of apoB and apoB-containing lipoproteins (15,16,18). The current work on the L343V mutation, together with the previous R463W studies (35), provides additional evidence for the functional importance of the ␤␣1 domain.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Transfection studies have suggested that apoB segments containing sequences lacking the ␤␣1 domain were unable to be secreted (13) or else secreted poorly (14). Mutational analysis has identified critical disulfide linkages within the ␤␣1 domain that are essential for efficient secretion of apoB and apoB-containing lipoproteins (15,16,18). The current work on the L343V mutation, together with the previous R463W studies (35), provides additional evidence for the functional importance of the ␤␣1 domain.…”
Section: Discussionmentioning
confidence: 62%
“…Transfection studies show that apoB segments lacking the ␤␣1 domain are either unable to be secreted (13) or poorly secreted (14). Mutagenesis experiments show that correct disulfide bond formation within the ␤␣1 domain is required for efficient secretion of apoB (15)(16)(17), and this requirement is independent of the lipidation state of apoB (18). The sequence elements involved in the physical interaction between apoB and its molecular chaperone, the microsomal triglyceride transfer protein (MTP), have been located to the ␤␣1 domain (19).…”
mentioning
confidence: 99%
“…This idea first emerged from the observation that the reduction of the disulfide bonds in the N-terminus blocked apoB secretion (22,23). Similar defects were reported when cysteine pairs were mutated to alanine or serine (24,25). More recently, two groups reported that in cells with MTP, apoB sequences as short as ∼20% of B100 were sufficient for the assembly of a lipoprotein particle containing neutral lipids (26,27).…”
mentioning
confidence: 87%
“…ApoB16 del and apoB34 del were prepared by the digestion of apoB16 and apoB34 expression vectors with EheI and BclI to liberate an oligonucleotide corresponding to the first 210 residues of apoB. Because it has been reported that the disulfide bond between cysteines 7 and 8 is critical for assembly and secretion of apoB-containing lipoproteins (31)(32), this disulfide was preserved in our apoB16 del and apoB34 del constructs. ApoB ␤ was created by directly linking the amphipathic ␤ strands between apoB28 and -B34 (21) to a signal peptide of apoB.…”
Section: Methodsmentioning
confidence: 99%